Drivers of 20th century sea‐level change in southern New Zealand determined from proxy and instrumental records. (8th March 2022) - Garrett, Ed; Gehrels, W. Roland; Hayward, Bruce W.; Newnham, Rewi; Gehrels, Maria J.; Morey, Craig J.; Dangendorf, Sönke
ABSTRACT: In this paper we present new proxy‐based sea‐level reconstructions for southern New Zealand spanning the last millennium. These palaeo sea‐level records usefully complement sparse Southern Hemisphere proxy and tide‐gauge sea‐level datasets and, in combination with instrumental observations, can test hypotheses about the drivers of 20th century global sea‐level change, including land‐based ice melt and regional sterodynamics. We develop sea‐level transfer functions from regional datasets of salt‐marsh foraminifera to establish a new proxy‐based sea‐level record at Mokomoko Inlet, at the southern tip of the South Island, and to improve the previously published sea‐level reconstruction at Pounawea, located about 110 km to the east. Chronologies are based on radiocarbon, radiocaesium, stable lead isotope and pollen analyses. Both records are in good agreement and show a rapid sea‐level rise in the first half of the 20th century that peaked in the 1940s. Previously reported discrepancies between proxy‐based sea‐level records and tide‐gauge records are partially reconciled by accounting for barystatic and sterodynamic components of regional sea‐level rise. We conclude that the rapid sea‐level rise during the mid‐20th century along the coast of southern New Zealand was primarily driven by regional thermal expansion and ocean dynamics.